NHRDF Red 4: new onion variety - Singh, R K; Dubey, B K; Gupta, P K (Indian Horticulture, 2019)
Onion NHRDF Red 4 is becoming popular among farmers due to its high yield, better adaptability and storage. This variety is tested at 5-6 locations in multilocational trials with other entries, local and the control during 2011-12 to 2013-14. Its average yield is best and recorded superior over all varieties.